Economics of law on the effectiveness of compensating social equilibrium - Belikova, Ksenia M. (Opción, 2019)
The article provides a scientific analysis of economic approaches reflected in economic doctrines on the effectiveness of compensating for social equilibrium while optimizing the costs of precautionary measures to prevent tort liability via the method of systematic analysis. As a result, the approach of French lawmakers seems to be interesting, having embarked on the path of supplementing the classical views on tort liability with new rules. In conclusion, the development of a standard of behavior will always accompany not only tort law from the perspective of both general approaches.